Sandwich-Style Anterior Cruciate Ligament Reconstruction: Double-Bundle Anterior Cruciate Ligament Reconstruction With In-Between Remnant Preservation - Jin Tang, B.M.; Jinzhong Zhao, M.D. (Arthroscopy Techniques, 2021)
Various degree of remnant tissues exists following anterior cruciate ligament (ACL) injury. Making use of these tissues may be helpful for the reconstructed ACL from many aspects. There are many methods of remnant preservation and use, as well as many types of combined ACL reconstruction. However, the most effective methods of remnant reuse as well as ACL reconstruction are still being pursued. We introduce an anatomical double-bundle transtibial ACL reconstruction with in-between remnant preservation technique named sandwich-style ACL reconstruction. The indication of this technique is complete ACL tear with a large volume of connectable remnant. The main tricks of this technique are proper ligation of the remnant, proper location of the anteromedial-bundle tibial tunnels, and passing the anteromedial bundle through the shallow side of the remnant. We believe the introduction of this technique will provide more options for remnant preservation and ACL reconstruction.